Graphite-epoxy composites for fuel-cell bipolar plates: Wet vs dry mixing and role of the design of experiment in the optimization of molding parameters. (19th January 2021) - Roncaglia, Fabrizio; Romagnoli, Marcello; Incudini, Simone; Santini, Elena; Imperato, Manuel; Spinelli, Luca; di Bona, Alessandro; Biagi, Roberto; Mucci, Adele
Abstract: Bipolar plates (BPs) are key components of Proton Exchange Membrane Fuel Cells mainly employed in hydrogen-powered electric vehicles. Here, a reliable and detailed experimental method to prepare graphite-epoxy composites suitable for manufacturing BPs is reported. Dry and wet mixing procedures were compared and a simple composition was optimized, with regard to electrical conductivity. The adoption of wet mixing of the components and the choice of the conductive filler were the main factors that contributed to the achievement of good electrical and mechanical properties. The addition of a small percentage of carbon black as a secondary filler was also advantageous. The effects of molding parameters (pressure, temperature and time) on a fixed-composition graphite-epoxy composite were modeled using a Design Of Experiments approach, which provided valuable information for future improvements. Conductivity values well above the US DOE requirements were obtained. Highlights: Bipolar plates with conductivity above US DOE were obtained from low cost materials. When an epoxy binder is used, processed graphite is preferred over natural graphite. Preparation by wet mixing is preferred over dry mixing the composite components. Design of Experiment gave useful hints for future improvements.